Comparison of Rifabutin-Based Versus Rifampin-Based Regimens for the Treatment of Mycobacterium avium Complex: A meta-Analysis Study - Hajikhani, Bahareh; Nasiri, Mohammad Javad; Adkinson, Brian C.; Azimi, Taher; Khalili, Farima; Goudarzi, Mehdi; Dadashi, Masoud; Murthi, Mukunthan; Mirsaeidi, Mehdi (Frontiers in Pharmacology, 2021)
Background: The incidence of Mycobacterium avium complex (MAC) increases as immunosuppressed conditions become more common. MAC's standard treatment regimen includes a macrolide, ethambutol, and a rifamycin, among which rifampin and rifabutin are the most commonly used. Although current guidelines recommend initial therapy for MAC with rifampin, it has been theorized to be less efficacious than rifabutin. Methods: We reviewed the relevant scientific literature published up to February 18, 2020. Statistical analyses were performed with Comprehensive Meta-Analysis Software Version 2.0 (Biostat, Englewood, NJ). The pooled frequency with 95% confidence intervals (CI) was assessed using a random-effect model. We considered P <0.05 as statistically significant for publication bias. Results: After reviewing 3665 records, we identified 24 studies that satisfied the inclusion criteria. Among these studies, 8 had rifabutin in their regimens (rifabutin group) and 16 had rifampin in their regimens (rifampin group). The estimated pooled treatment success rate was found to be 54.7% (95% CI 41.0-67.0%) in rifabutin groups and 67.5% (95% CI 55.7-77.4%) in rifampin groups. There was no evidence of publication bias among the included studies (Egger’s test p-value was 0.7). Conclusions: The results suggest that the treatment success rate for MAC of rifampin is not inferior to rifabutin. Based on our study results, rifampin may even be superior to rifabutin for MAC treatment.